Nanoplate like heterostructured BiOBr/BiBr/FeBr2 nanocomposites with enhanced photocatalytic activity for wastewater treatment by removing organic dyes: Interfacial consecutive dual Z scheme electron transfer. Issue 2 (April 2022) - Mondal, Moumita; Halder, Mithun; Pradhan, S.K.
Abstract: Visible light-driven photocatalyst has been studied worldwide for wastewater treatment. In the present study, nanoplate-like heterostructured BiOBr/FeBr2 /BiBr (BFB-a, b, c) novel photocatalysts have been synthesized by fine-tuning the pH ( 6.46, 7.71, 9.16 for BFB- a, b, c samples, respectively) of the solution employing a facile water-bath method. Different physicochemical processes have been employed to characterize these heterostructured materials. The photocatalytic activity of the synthesized nanocomposites has been primarily investigated with the aqueous solution of an organic dye Rhodamine B (RhB) under visible light illumination. It is noticed that the photodegradation efficiency of synthesized nanocomposites has been significantly enhanced compared to the pure BiOBr compound. The photocatalytic activity also increases 3 times with the increasing pH value. The BFB-c nanocomposite shows 81% RhB degradation within 120 min under visible light and 100% degradation with 0.1 mL of isopropyl alcohol. Scavenger tests have identified the proper radical of the photocatalytic reaction. The faster rate of the photocatalytic process has been interpreted by the interfacial consecutive dual Z scheme electron transfer mechanism. This photocatalytic technique has also been successfully applied to Methylene Blue (MB) and Methyl Orange (MO)organic dyes. The BFB nanocomposites can be used as an efficient visible-light-driven photocatalyst for the photodegradation of organic dye pollutants dissolved in wastewater. Graphical Abstract: ga1 Highlights: Heterostructured Bi-Fe-Br-O nanocomposites are synthesized by water bath method. Microstructure and morphology are tuned by pH control. Microstructure, morphology, bandgap are revealed by XRD, FESEM, TEM, UV–Vis. 100% photocatalytic degradation of RhB is achieved within 120 min Photocatalytic degradation efficiency is correlated with Urbach energy.